Evaluación del estado trófico en aguas superficiales de uso agrícola de la microcuenca del Río Palenque - Olaya Siguenza, Erick Alexander (Machala : Universidad Técnica de Machala, 2021)
The River Palenque form splits of the slopes of the peaceful that originates between the mountain ranges of Chilla and Campo Real which has an approximate length of 23 km before forming part of the Estero Motuche, being his final disposal, the channel of Jambelí. His discharge is allocated for agricultural use or irrigation, although it also resupplies of water to rural communities like Real Field or the parish Palenque. The river characterizes for possessing a little deep basin, be under the influence of the agricultural sector and especially the pollution caused by the download indiscriminada of waters no debugged originated in the lagoons of oxidation of the sector La Sabana, and El Cangrejo of Pasaje city. The aim of the study consists in comparing the parameters analyzed with the rule of environmental quality and of downloads of effluents of the resource waters established in the TULSMA, edition Number 387 of the year 2015, as well as evaluate the state trófico in each one of the stations of sampling of the microcuenca, selected strategically using the application google Maps. The study was divided in 6 campaigns of sampling during the coldest period in the province of El Oro, selected 5 stations of sampling along the route of the microcuenca, taking in account the points of download, or channels manifolds of populated like Campo Real, Palenque, of urban zones of Pasaje city and the agricultural sector that converge in the microcuenca causing environmental alterations.
El Río Palenque forma parte de las vertientes del pacífico que se origina entre las cordilleras de Chilla y Campo Real el cual tiene una longitud aproximada de 23 km antes de formar parte del Estero Motuche, siendo su disposición final, el canal de Jambelí. Su caudal es destinado para uso agrícola o riego, aunque también abastece de agua a comunidades rurales como Campo Real o la parroquia Palenque. El río se caracteriza por poseer una cuenca poco profunda, estar bajo la influencia del sector agrícola y sobre todo la contaminación provocada por la descarga indiscriminada de aguas no depuradas originadas en las lagunas de oxidación del sector La Sabana, y El Cangrejo de la cuidad de Pasaje. El objetivo del estudio consiste en comparar los parámetros analizados con la normativa de calidad ambiental y de descargas de efluentes del recurso agua establecida en el TULSMA, edición Nº 387 del año 2015, así como evaluar el estado trófico en cada una de las estaciones de muestreo de la microcuenca, seleccionados estratégicamente usando la aplicación google Maps. El estudio fue dividido en 6 campañas de muestreo durante la época más fría en la provincia de El Oro, se seleccionaron 5 estaciones de muestreo a lo largo del recorrido de la microcuenca, tomando en cuenta los puntos de descarga, o canales colectores de poblados como Campo real, Palenque, de zonas urbanas de la cuidad de Pasaje y el sector agrícola que convergen en la microcuenca causando alteraciones medioambientales.
Keywords: EUTROFIZACION; ESTADO TROFICO; RIO PALENQUE; LAGUNA DE OXIDACION